Latvijas Universitātes zinātne laikmeta liecībās - Saviča, Mārīte (My University, 2007)
The Library of the University of Latvia is the curator and provider of intellectual values of the University of Latvia. In the article are analyzed the action trend in the information resources accessibility and management, what consummate with abundant traditions from the preceding years and will least in after years, using different forms of popularization of the information accessibility, of the Library.
Research at the Unifersity of Latvia
Keywords: zinātne; Latvijas Universitāte; piekļuve; informācijas resursi